Multidimensional dataset for cognitive assessment, sMRI, and rsfMRI in common benign epileptic children - Hongzhou Chen; Mengyuan Li; Tian Li; Mai Chen; Chao Jiang; Yudian Tang; Qian Chen; Dazhi Cheng (Scientific Data)
Abstract Recent studies have highlighted the potential association between common benign epilepsy syndromes in children and the development of partial cognitive impairment. We established a comprehensive database of cognitive, structural magnetic resonance imaging (sMRI), and resting-state functional magnetic resonance imaging (rsfMRI) data obtained from a cohort of 36 Chinese paediatric volunteers. The participants, aged 5–16 years, were specifically diagnosed with either benign epilepsy with centrotemporal spikes (BECTs) or childhood absence epilepsy by certified paediatric neurologists. All imaging data were collected by qualified clinicians, and cognitive data were collected within 1 year of magnetic resonance imaging data collection. This database allows researchers to perform more detailed analyses using multimodal data to explore the relationship between cognitive impairment and brain mechanisms in children with common epilepsy syndromes.